HUBUNGAN PROCALSITONIN DAN GAMBARAN MORFOLOGI LEUKOSIT PADA INFEKSI BAKTERIAL - Fenty Fenty; Dita Maria Virginia (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2014)
Abstract: Bacterial sepsis increases morbidity and mortality in all ages. Early detection has been shownto be crucial for the improved outcome of patients with sepsis. Till now there is no routine test forscreening. Procalcitonin and morphology of leukocytes are biomarkers of bacterial sepsis. The aim of thisstudy was to determine the relationship between procalcitonin and morphology of leukocytes as marker inbacterial infection. This study was analytical observational with cross sectional design and data collectedprospectively.This study measured simultaneously the value of procalcitonin and morphology of leukocytesexamination in patients with suspected bacterial infection in hospital X of Yogyakarta. Data were analysedby statistics. The results showed immature granulocytes and vacuolization of neutrophils in the leucocytesmorphology has a significant correlation with level of procalcitonin.Keywords: bacterial infection, procalcitonin, morphology of leukocytes